The Strategic Role of Halal Values and Brand Image in Building Customer Trust and Satisfaction - Faigah A Badjamal; Zakiya Zahara; Syamsul Bachri; Syamsul Bahri Dg. Parani; Muzakir; Maskuri Sutomo (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The growth of digital technology and rising awareness of halal values have transformed marketing strategies in the culinary industry, particularly for medium-sized businesses. These businesses, typically employing 10–50 staff or generating in annual revenue, face unique challenges in building customer trust. This study aims to evaluate how social media marketing, halal value, brand image, product innovation, and customer satisfaction contribute to trust in medium-sized culinary businesses and to develop a conceptual framework. A systematic literature review was conducted, analyzing 71 articles from 412, published between 2014 and 2024, using the PRISMA framework. The findings show that innovative products, engaging social media content, consistent brand image, and transparent halal practices enhance customer satisfaction, which strengthens trust. Satisfaction acts as a key link, connecting these factors to customer loyalty through positive experiences. The study highlights that medium-sized culinary businesses can build strong customer connections by aligning strategies with local values and consumer needs. In conclusion, this research offers a new framework for understanding trust-building in culinary businesses and provides practical strategies, such as using social media to share halal certifications and innovative menus, to foster loyalty.